Konflik batin tokoh utama dalam novel Trauma karya Boy Candra - Bagus Dinda Sakti; Sri Muryati; Bernika Mahalini Wijaya; Vincencia Lucky Kriswidyasari (Jurnal Komunitas Bahasa, 2023)
Literary work is a creative or innovative world created by the author after contemplating the social environment of his life. The purpose of this study is to describe the form of inner conflict in Boy Candra's novel Trauma. This research is aqualitative research with content analysis method. The data collection technique uses literature study techniques, namely reading repeatedly and carefully in order to fully understand the meaning. The results of this study describe the forms of conflict in Boy Candra's novel Trauma, showing several kinds of inner conflict which include sadness, worry, fear, and disappointment.